2008
DOI: 10.1177/00333549081230s314
|View full text |Cite
|
Sign up to set email alerts
|

HIV Risk Behaviors and Testing History in Historically Black College and University Settings

Abstract: Objectives. From 2001 through 2005, African Americans accounted for the largest percentage of new cases of human immunodeficiency virus (HIV)/ acquired immunodeficiency syndrome (AIDS) in all age categories, especially among people aged 13 to 24 years. Although students attending historically black colleges and universities (HBCUs) report many of the behaviors that promote HIV transmission, their risk behaviors and HIV testing practices have not been well-characterized. We compared the demographic and behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 8 publications
3
62
0
1
Order By: Relevance
“…There were incidents of some form of sexual assault, which could have had an effect on one's self-esteem or body image. Thomas et al (2008) noted that religiosity has an effect on sexual risks taken by African-American females. The survey illustrated that CAU female students deemed spirituality as an important aspect of sexuality/sexual health, along with sexual health care and safer sex.…”
Section: Resultsmentioning
confidence: 99%
“…There were incidents of some form of sexual assault, which could have had an effect on one's self-esteem or body image. Thomas et al (2008) noted that religiosity has an effect on sexual risks taken by African-American females. The survey illustrated that CAU female students deemed spirituality as an important aspect of sexuality/sexual health, along with sexual health care and safer sex.…”
Section: Resultsmentioning
confidence: 99%
“…Data from the United States of America has shown that among youths aged 13 -19 years, 57% of reported infections occurred among women and 43% among young men while among youths aged 20 -24 years, 64% of reported HIV infections occurred among young men and 36% among young women [20]. From 2001 through 2005, it has been reported that African Americans had the largest percentage of new cases of Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Virus (AIDS) in all age categories, especially among people aged 13 -24 years [21].…”
Section: O a Okoli Et Al 262mentioning
confidence: 99%
“…Testing for HIV can serve as a bridge for providing early treatment and encouraging behavior change among people already infected with HIV or at risk of HIV infection [6,[21][22][23]. Enlightenment campaigns on HIV/ AIDS and education programme on safe sex and behavior change among fresh students of university remain key responses to the epidemic [6,24].…”
Section: O a Okoli Et Al 262mentioning
confidence: 99%
“…31,33,34 Thirty percent of people tested in the nonclinical settings project, 34% of inmates tested in the corrections project, and 42% of people surveyed and tested at HBCUs in the HBCU/alternative venues project had never before been tested for HIV. [33][34][35] Among TG people who were tested in the HBCU/alternative settings project, 36 93% self-identified as male-tofemale (MTF) TG and 7% as female-to-male (FTM) TG. Only 8% of MTF TG participants had never been tested for HIV, but 37% reported unprotected receptive anal intercourse in the preceding 12 months.…”
Section: Data On Hiv Testing Servicesmentioning
confidence: 99%
“…30,31,35,36,38,41 Use of findings to guide policy decisions and recommendations Knowledge gained during these projects informed activities of CDC's Division of HIV/AIDS Prevention to (1) increase the proportion of HIV-infected people who know their HIV serostatus by improving access to HIV testing services in community and health-care settings, (2) reduce disparities in access to and use of testing services, and (3) increase linkage to care for people who are identified with HIV infection. Findings from these projects were used to help develop CDC's revised recommendations for HIV testing in health-care settings in 2006, 42 and the HIV counseling and testing section of CDC's provisional procedural guidance for CBOs.…”
Section: Dissemination Of Findingsmentioning
confidence: 99%